PREVENTIVE STRATEGIES FOR RECURRENT URINARY TRACT INFECTIONS: THE ROLE OF DIET AND NON-ANTIBIOTIC AGENTS - Martyna Różańska; Bartłomiej Kusy; Agnieszka Bajkacz; Karolina Niewola; Michał Robak; Marcin Płonka; Maciej Dudziński; Hanna Ćwirko (International Journal of Innovative Technologies in Social Science, 2025)
Background: Recurrent urinary tract infections remain a significant clinical and public health concern due to their high prevalence, considerable recurrence rates, and the growing challenge of antimicrobial resistance. In light of the limitations associated with long-term antibiotic use, non-antibiotic prophylactic strategies have garnered increasing interest. This review synthesizes current evidence on the efficacy of various non-antibiotic interventions, including behavioral and dietary modifications, probiotics, cranberry products, D-mannose, methenamine hippurate, topical vaginal estrogen, and immunoprophylaxis.Aim: This study aims to introduce non-antibiotic approaches to the prevention of recurrent urinary tract infections and to highlight how their integration into clinical practice may decrease reliance on antibiotics and improve long-term patient outcomes.Methods: This narrative review synthesizes current research findings on the topic. The literature search was conducted using PubMed and Google Scholar database, focusing on recent studies relevant to non-antibiotic strategies for the prevention of recurrent urinary tract infections.